The fleets on the northern frontier of the Roman empire from the 1st to 3rd century - Rummel, Christoph (2008)
Ancient sources consistently identify a strong naval element to Roman military activity along the northern frontier from the earliest occupation campaigns to Late Antiquity. This element is formed by four established provincial fleets, the CLASSES BRITANNICA, GERMANICA, PANNONICA and MOESICA. The current understanding of these units, however, is disproportionate to their importance and some current interpretations are in urgent need of revision in view of new archaeological and epigraphic data relevant to the fleets.